2018
DOI: 10.1002/cne.24506
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ErbB4 in parvalbumin‐positive interneurons inhibits adult hippocampal neurogenesis through down‐regulating BDNF/TrkB expression

Abstract: Parvalbumin (PV) positive interneurons in the subgranular zone (SGZ) can regulate adult hippocampal neurogenesis. ErbB4 is mainly expressed in PV neurons in the hippocampus and is crucial for keeping normal function of PV neurons. However, whether ErbB4 in PV interneurons affects the adult hippocampal neurogenesis remains unknown. In the present study, we deleted ErbB4 specifically in PV neurons by crossing PV‐Cre mice with ErbB4f/f mice. Results of BrdU labeling and NeuN staining revealed that the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 70 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…The membrane and cytoplasm of PV interneurons in the DG of control mice were strongly immunoreactive by immunostaining, having a fusiform or elliptical shape ( Figure 6E). Post hoc analysis revealed that ErbB4 ablation significantly decreased PV-positive cells number (Figure 6F), which is in line with previous reports (Chen et al, 2010;Tian et al, 2017;Zhang et al, 2018). PV-ErbB4 −/− mice subjected to treadmill running (PV-ErbB4 −/− + run) increased the number of PV-positive interneurons when compared to those corresponding model mice (PV-ErbB4 −/− + static) ( Figure 6F).…”
Section: Treadmill Running Increases Neurogenesis and Pv-positive Intsupporting
confidence: 91%
See 1 more Smart Citation
“…The membrane and cytoplasm of PV interneurons in the DG of control mice were strongly immunoreactive by immunostaining, having a fusiform or elliptical shape ( Figure 6E). Post hoc analysis revealed that ErbB4 ablation significantly decreased PV-positive cells number (Figure 6F), which is in line with previous reports (Chen et al, 2010;Tian et al, 2017;Zhang et al, 2018). PV-ErbB4 −/− mice subjected to treadmill running (PV-ErbB4 −/− + run) increased the number of PV-positive interneurons when compared to those corresponding model mice (PV-ErbB4 −/− + static) ( Figure 6F).…”
Section: Treadmill Running Increases Neurogenesis and Pv-positive Intsupporting
confidence: 91%
“…PV-ErbB4 −/− mice subjected to treadmill running (PV-ErbB4 −/− + run) increased the number of PV-positive interneurons when compared to those corresponding model mice (PV-ErbB4 −/− + static) ( Figure 6F). ErbB4 ablation in PV interneurons sharply increase the proliferation of NSCs in the hippocampus (Figures 6G,H), in line with previous reports using BrdU labeling (Zhang et al, 2018). Moreover, PV-ErbB4 −/− mice subjected to treadmill running significantly increased the number of Ki67-positive cells in the DG (Figure 6H).…”
Section: Treadmill Running Increases Neurogenesis and Pv-positive Intsupporting
confidence: 91%
“…Furthermore, citalopram administration decreases the quantity of newly generated Aβ in young healthy humans (Sheline et al, 2014). Clinical studies indicate that citalopram has therapeutic effects in AD patients, including rescuing non-cognitive neuropsychiatric behaviors such as depression, anxiety, irritability, and apathy (Zhang H. et al, 2018), although the benefits on agitation and cognition remain controversial (Siddique et al, 2009;Porsteinsson et al, 2014). Results from socially isolated rats suggested that citalopram improves learning and memory by promoting synaptic plasticity and hippocampal neurogenesis (Gong et al, 2017).…”
Section: Targeting Increased Numbers Of Gaba Inhibitory Interneuronsmentioning
confidence: 99%
“…Recent studies demonstrated that ErbB4 protein knockdown in PV inhibitory interneurons significantly increased LTP and improved memory ability in hAPP-J20 mice without changing Aβ plaque deposition (Zhang et al, 2017). One plausible mechanism for this is that ErbB4 ablation increases PV inhibitory interneuron activity (Zhang et al, 2017;Zhang H. et al, 2018), although this requires further confirmation. By regulating GAD67 expression in GABA inhibitory interneurons, half-quantity expression of GAD67 significantly reduced Aβ deposition and improved cognitive performance in 5xFAD mice due to elevated GABA inhibitory interneuron activity (Wang et al, 2017a).…”
Section: Targets To Improve Gaba Inhibitory Interneuron Activitymentioning
confidence: 99%
“…Neurotrophic factor neuregulin 1 and its receptor ErbB4 are susceptibility genes of schizophrenia and bipolar disorders [8,9]. ErbB4 is exclusively expressed in GABAergic interneurons in hippocampus, and mainly in parvalbumin positive type, regulating the spine formation and synaptic plasticity in glutamatergic neurons [10,11], specifically knockout ErbB4 in parvalbumin interneurons is enough to induce cognitive impairments and inhibits adult hippocampus neurogenesis [12]. Exercise can increase neuregulin 1/ErbB signaling in skeletal and cardiac muscle and promote muscle repairment [13,14], we also observed exercise could increase ErbB4 expression in hippocampus, but whether neuregulin1/ErbB signaling mediates exercise effects on adult neurogenesis is still unknown.…”
Section: Introductionmentioning
confidence: 99%